Affective Organizational Commitment and Turnover Intention of academics in Malaysia - Lew, Tek (Institute of Electrical and Electronics Engineers, Inc., 2010)
This study aims to test the structural model that explains the relationships between career development opportunities,POS, felt obligation, affective organizational commitment and turnover intention of academics working for one of the foreignoffshore campuses of Australian universities in Malaysia. This study is driven theoretically by the social exchange theory and theorganizational support theory. The survey method and the structural equation modeling (SEM) data analysis method wereused. The proposed structural model was supported by this study.